Dietary diversity, eating habits, dietary patterns, food choice, and associated factors among adolescent girls: a convergent parallel mixed-method study in the Mion District of Ghana - Raihana Al-Hassan; Mavis A. Ayimbire; Ambrose Atosona; Humphrey Garti; Anthony Wemakor; Inge D. Brouwer; Fusta Azupogo (Journal of Nutritional Science)
Understanding adolescents’ diet and eating behaviours is crucial for informing public health strategies and policies, allowing interventions to be tailored effectively to enhance dietary patterns and improve overall health and quality of life. This study examined dietary patterns, dietary diversity, eating habits, food choice and the factors influencing these among adolescent girls in the Mion District, Ghana. A convergent parallel mixed-method design employing in-depth interviews (n = 30), two focus group discussions (n = 10) and survey data from 882 mother-daughter pairs was used. Key findings indicate that approximately 90% of girls achieved the minimum dietary diversity for women of reproductive age (MDD-W), with most consuming three meals daily. Staples were eaten daily, while fruits and unhealthy foods were less frequently eaten. Moderate/severe food insecurity was negatively associated with the MDD-W, whereas larger household size was positively correlated with the MDD-W. Older girls were less likely to eat breakfast, while household crop farm diversity increased the odds of eating supper on weekends. Moderate/severe food insecurity was inversely associated with intake of animal-sourced foods (ASFs), fruit, and unhealthy foods but positively correlated with vegetable consumption in the past month. Maternal non-literacy was linked to a lower intake of unhealthy foods, while specific ethnic backgrounds negatively influenced ASF intake. Wealthier households demonstrated higher consumption of staples. Qualitatively, health considerations, availability, taste, and cravings were major influencers of food choices. Food aversions were often tied to intolerance, fatigue from consuming the same foods repeatedly, and preferences related to taste and texture. These findings underscore the need for targeted nutritional interventions considering socio-economic and household factors to improve adolescent girls’ dietary habits and overall health.